Evaluation of Diagnostic Utility of Immunohistochemistry Markers of TROP-2 and HBME-1 in the Diagnosis of Thyroid Carcinoma. Issue 1 (22nd January 2019) - Zargari, Nooshin; Mokhtari, Maral
Abstract : Objective: The diagnosis of thyroid tumors is based on histologic features, but the distinction between benign and malignant thyroid lesions is somehow difficult, especially in lesions with a follicular pattern. Thus, ancillary studies, such as immunohistochemistry (IHC), may be helpful. In this study, we aimed to evaluate the diagnostic value of 2 IHC markers, TROP-2 and HBME-1, in the diagnosis of thyroid cancers. Study Design: A total of 102 cases of thyroid lesions, including papillary thyroid carcinoma (classic variant) (29 cases), follicular variant of papillary thyroid carcinoma (21 cases), multinodular goiter (22 cases), follicular adenoma (24 cases), and follicular carcinoma (6 cases) were selected. The hematoxylin-eosin slides were reviewed for confirmation of diagnosis, and IHC examination for TROP-2 and HBME-1 was performed. Result: HBME-1 had 84% sensitivity and 98% specificity with a positive predictive value (PPV) of 98% and a negative predictive value (NPV) of 83%. TROP-2 had 93% sensitivity and 74% specificity with a PPV of 81% and an NPV of 90% in malignant thyroid lesions. Conclusion: IHC panel consisting of TROP-2 and HBME-1 can be used in equivocal follicular patterned lesions for the diagnosis of thyroid carcinomas.